MINERALOGICAL, PETROGRAPHIC AND GEOCHEMICAL EVIDENCE FOR ZIRCON FORMATION CONDITIONS WITHIN THE BURPALA MASSIF, NORTHERN BAIKAL REGION - A. E. Starikova; A. V. Malyutina; I. A. Izbrodin; A. G. Doroshkevich; T. A. Radomskaya; A. T. Isakova; D. V. Semenova; A. V. Korsakov (Геодинамика и тектонофизика, 2024)
This paper reports investigation on zircons from quartz syenite, alkaline and foid syenite, as well as metasomatic rock from the fenitization zone hosted by the Burpala massif. It is performed by scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDS), cathodoluminescence (CL), laser ablation inductively coupled plasma mass spectrometry (LA ICP MS), and Raman spectroscopy. Generally, all zircons from igneous rocks show rhythmic, crystal growth zoning or sector zoning (type I) except for some zircons from alkaline syenites (type II) showing patchy zoning. They systematically contain pores or cavities. The REE patterns of magmatic zircons share similar features: e.g. depletion of LREE ((Yb/La)N up to 35000), large positive Ce (Ce/Ce* 6–427) and small negative Eu (Eu/Eu* 0.37–0.93) anomalies. Zircons crystallized from quartz syenites at 830±30 °C at the early stage of rock formation, while zircons from alkaline and foid syenites crystallized at the later stage of rock formation (680–750 °C). Meanwhile, crystallization of zircons with rhythmic zoning (type I) occurs at later magmatic stage, while the formation zircons of type II is probably related to the separation of the highly fluorinated aqueous fluid from the residual melt.Zircons from fenites have a bipyramidal habit holding a heterogeneous mosaic core and a homogeneous (or rhythmic zoning) rim. The cores of zircon show flat REE patterns without significant anomalies, while the rims are characterized by noticeable fractionation of REE ((Yb/La)N 85–615) and show a positive Ce anomaly (Ce/Ce* 4–18). The Raman spectra of the cores show a higher degree of crystallinity than the rims, and their flat REE spectra are probably related to the contamination by micro inclusions. The discordant U-Pb age of 295±3 Ma was obtained for zircon rims, which is consistent with the age of formation of igneous rocks of the Burpala massif (298–291 Ma). The latter supports the syngenetic origin of metasomatic ore mineralization with the main stage of massif formation.